ADHERENCE TO MANAGEMENT IN PATIENTS WITH END STAGE RENAL DISEASE - Raashid, Sheharyar; Arshad, Abdul Rehman; Mir, Abdul Wahab (Pakistan Armed Forces Medical Journal, 2021)
Objective: To document overall adherence to haemodialysis, medications, fluid restriction and dietary prescription in patients with end-stage renal disease and to study factors that could predict poor adherence. Study Design: Cross-sectional analytical study. Place and Duration of Study: Department of Nephrology, Pak Emirates Military Hospital, Rawalpindi, from Jul to Sep 2018. Methodology: Adult patients on haemodialysis for at least three months were selected using consecutive sampling technique. Patients with acute kidney injury, patients on haemodialysis for less than 3 months, those on infrequent haemodialysis and unwilling patients were excluded. Demographic data was recorded. Adherence to management was assessed by administering End Stage Renal Disease Adherence Questionnaire in direct face- to-face interviews. Results: There were a total of 101 patients having a mean age of 51.05 ± 13.80 years. Median haemodialysis vintage was 9 months (interquartile range 3-24 months). Mean adherence scores were 970.54 ± 149.43. Mean perception scores were 7.22 ± 1.37. Only 49 (48.51%) patients had good adherence, whereas 52 (51.49%) had poor adherence to management. Increasing age was associated with poor adherence (β=-0.038; Odds Ratio=0.963, 95% CI 0.928- 1.000, p=0.048). No other demographic parameter could predict poor adherence. Conclusion: Non-adherence to different aspects of management plan was a significant problem, more so in younger patients.